Problem solving with C++ - Savitch, Walter J. , 1943- (Pearson Addison Wesley, 2012)
1. Introduction to computers and C++ programming -- 2. C++ basics -- 3. More flow of control -- 4. Prodedural abstraction and functions that return a value -- 5. Functions for all subtasks -- 6. I/O streams as an introduction to objects and classes -- 7. Arrays -- 8. Strings and vectors -- 9. Pointers and dynamic arrays -- 10. Defining classes -- 11. Friends, overloaded operators, and arrays in classes -- 12. Separate compilation and namespaces -- 13. Pointers and linked lists -- 14. Recursion -- 15. Inheritance -- 16. Exception handling -- 17. Templates -- 18. Standard template library